White collar crime: the study on the law of insider trading in Malaysia / Abdul Hakeem Ainman Mohd Affandi … [et al.] - Mohd Affandi, Abdul Hakeem Aiman; Sahak, Ahmad Saiful Bahari; Mohd Othman, Syamil; Abdul Jalal, Wan Ikhwan (2010)
The research that has been conducted is on the law of insider trading in Malaysia. Generally, insider is one of the white collar crimes which is growing all around the world. The research looks on how actually the Malaysian government tackles the issue compare with other various approaches that have been taken in Australia, United States of America, Singapore and Hong Kong. The aim of this research is to identify the problems on the law of insider trading in Malaysia and to propose recommendations to overcome those problems.